INKLUSI KEUANGAN DAN PENYALURAN KREDIT UMKM DI JAWA TENGAH - Astiwi Indriani; Prasetiono Prasetiono; Shoimatul Fitria (JURNAL STUDI MANAJEMEN ORGANISASI, 2019)
Financial inclusion is currently a concern of the world and particularly the nation of Indonesia. Financial inclusion is expected to be able to provide access to financial services to the public. Banking financial services through lending can certainly support MSMEs in running their business. This investigation expects to examine the dimensions of financial inclusion, in particular the dimension of access and use, through indicators of demographic branch penetration, geographic ATM penetration, and Credit accounts per capita on the amount of MSME credit in Central Java. The sample in this research is using total sampling method. The sample used is 35 districts and cities in Central Java in 2011-2016. Data analysis used multiple linear regression analysis and classical assumption test. The outcomes showed that the demographic ATM penetration and credit accounts per capita had a significant positive effect on MSME credit, while the geographic branch penetration variable was not in accordance with the proposed hypothesis where geographic branch penetration had a negative and insignificant effect on MSME credit.